Types and Abundance of Peripyhton attached in the used tyre pieces Placed in The Air Hitam River, Pekanbaru City, Riau Province - Agfin Septian Yogi Pratama; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPeriphyton is a sessile microscopic organism that attach on submerged substrates. A research aims to determine the type and abundance of periphyton attached in theusedtyre pieces placed in the Air Hitam River substrate has been carried out in April-May 2018. There were three sampling stations, namely S1 (in the upstream), S2 (in the middle) and S3 (in the downstream). Samplings were conducted once/week for a 3 weeks period. The periphyton samples are brushed from the used tyre substrates (8 x 6) cm2. The number of tyre pieces in the S1, S2 and S3 were 12, 9, and 6 pieces respectively. Water quality parameter measured were water current, temperature, transparency, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate. Results shown that there were 29 types of periphyton present and they were belonged to 4 classes, namely Bacillariophyceae (15 species), Cyanophyceae (3 species), Chlorophyceae (8species), and Euglenaphyceae (3 species). The abundance of periphyton in the tyre substrate in the S1 was 15.119 cells/cm2, in the S2 was 37.245 cells/cm2and in the S3 was 70.029 cells/cm2. The water quality parameters were as follows: water current 0.08-0.46 m/s, transparency:18-29 cm, temperature 29-29.3oC, dissolved oxygen 3.43-3.56 mg/L, free carbon dioxide 6.2-7.9 mg/L, nitrate 0.302-0.529 mg/L, phosphate 0.348-0.542 mg/L. Data obtained indicate the the water quality of the Air Hitam River  is suitable to support the life of periphyton. Keywords:Type and abundance, sessile organism, aquatic algae, rubber subtrate